2020
DOI: 10.2147/ndt.s280485
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association Between Autistic Symptoms and Self-Stigma in Patients with Schizophrenia Spectrum Disorders</p>

Abstract: Purpose Self-stigma negatively influences self-esteem, quality of life, self-efficacy, treatment adherence, and recovery in psychiatric patients. By revealing personality traits that influence self-stigma, we can gain useful knowledge for the management of self-stigma. A previous meta-analysis indicated that patients with schizophrenia have higher scores on the Autism-Spectrum Quotient (AQ) than healthy controls. However, the relationship between autistic symptoms and self-stigma in patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
1
10
1
Order By: Relevance
“…One previous report showed that the age of onset was lower in patients with schizophrenia-spectrum disorders who had autism-spectrum disorders than in those without such disorders [31]. The results of this study indicated that a younger age of onset among patients with schizophrenia-spectrum disorders was associated with a higher AQ total score, which is consistent with the results of previous studies [21,31]. We identified a weak positive correlation between age at onset and the QIDS score in the bivariate correlation analysis.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…One previous report showed that the age of onset was lower in patients with schizophrenia-spectrum disorders who had autism-spectrum disorders than in those without such disorders [31]. The results of this study indicated that a younger age of onset among patients with schizophrenia-spectrum disorders was associated with a higher AQ total score, which is consistent with the results of previous studies [21,31]. We identified a weak positive correlation between age at onset and the QIDS score in the bivariate correlation analysis.…”
Section: Discussionsupporting
confidence: 91%
“…One previous study revealed a significant association between autistic symptoms and self-stigma in with schizophrenia-spectrum disorders [21]. Considering that prior studies have shown that self-stigma is associated with depressive symptoms and recovery, we hypothesized that autistic symptoms would also directly or indirectly correlate with self-stigma, depressive symptoms, and recovery.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations